Penerapan Certainty factor pada Rancang Bangun Sistem Pakar Deteksi Organisme Pengganggu Tanaman (OPT) Semangka - Agus Sifaunajah; Tholib Hariono; Moch. Chumaid (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2018)
Expert systems are applications that have the ability to mimic the reasoning of an expert based on his expertise in a knowledge. In this study, an expert system was designed to identify watermelon plant disturbing organisms. In this study, the author implements certainty factor in designing an expert system to identify watermelon plant disturbing organisms by providing rules of symptoms and providing value to each symptom obtained from an expert. All values obtained are processed using the certainty factor formula. The system built is also quite easy to use even by ordinary users. Its use is done by selecting the symptom data displayed by the system after all the displayed symptoms are selected by ticking it will immediately exit the identification results and see what percentage of the possibilities. Thus, watermelon farmers can do treatment, counseling or early prevention of their water plants. Keywords: Expert Sistem; Watermelon Plant Disease; Certainty Factor.